Aeroplane View of Site of the Exposition, New York World's Fair 1939 (Curt Teich & Co.)
This picture is taken from a plane looking down on Flushing Meadow Park, Queens, site of New York World's Fair, which is indicated by a heavy dotted line. The exhibit section occupies all of the area between the Long Island Railroad and the Horace Harding Boulevard. To the northwest may be seen the George Washington Bridge, while at the extreme left is the Triborough Bridge from Manhattan and the Bronx.